Harnessing technology to improve the consumer experience - Singapore Management University (Institutional Knowledge at Singapore Management University, 2017)
Professor Guo Zhiling is studying the impact of information technology on consumer behaviour and business strategy. See the papers: Assessing the impact of recommendation agents on on-line consumer unplanned purchase behavior Assessing the moderating effect of consumer product knowledge and online shopping experience on using recommendation agents for customer loyalty